2022
DOI: 10.1111/eje.12760
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of dental students’ performance in clinical courses based on their performance in pre‐clinical and academic courses

Abstract: Objectives Some dental schools depend on the students’ academic performance for admission purposes. This research aimed at investigating the correlations between dental students’ performance in specific academic courses and their pre‐clinical and clinical counterparts and the correlations between students’ performance in the pre‐clinical practical courses and the clinical courses. Methods Academic and practical pre‐clinical and clinical grades were retrieved for 811 students who graduated from the School of De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The lack of relationship between first-year preclinical science GPA as well as firstyear preclinical laboratory GPA and overall clinical science GPA supports previous research indicating a lack of relationship between preclinical and clinical performance. 3,11 However, it is in contrast to previous research that suggests that clinical performance may be predicted by preclinical performance, 10 particularly in operative dentistry 7,9 and fixed prosthodontics. 7,8 Further investigations on the genesis of student success in the latter years of the predoctoral dental program are warranted.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The lack of relationship between first-year preclinical science GPA as well as firstyear preclinical laboratory GPA and overall clinical science GPA supports previous research indicating a lack of relationship between preclinical and clinical performance. 3,11 However, it is in contrast to previous research that suggests that clinical performance may be predicted by preclinical performance, 10 particularly in operative dentistry 7,9 and fixed prosthodontics. 7,8 Further investigations on the genesis of student success in the latter years of the predoctoral dental program are warranted.…”
Section: Discussionmentioning
confidence: 91%
“…In contemplating the factors impacting student success in clinical courses, non‐cognitive factors should be evaluated. Factors of intrinsic manual dexterity and artistic talent have been referenced in literature discussing the relationship between preclinical and clinical outcomes 10 . Other studies have suggested a further investigation into non‐cognitive predictors of success in the clinical arena, including intrinsic psychological factors such as motivation and skills that may be, to some degree, taught, such as communication skills 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations